Pengembangan Sistem Informasi Manajemen Keuangan Sekolah berbasis Web menggunakan Whatsapp Gateway - Nur Abidin; Anwar Aini; Muhammad Izzuddin (Jurnal Informatika Terpadu, 2023)
The rapid development of information and communication technology supported by adequate and competent human resources is expected to create an information technology capable of solving school administration problems. The school financial management system at Mamba’ul Ihsan Banyuurip Vocational School still uses a recording system on payment cards and then manually recapitulates payment data in books. This causes the process to take quite a long time and has a risk of data loss or damage. This study aims to develop an information system to facilitate school finance parties in transactions and managing school financial data. In addition, the information system created can provide notifications to student guardians for notifications. System design is based on object-oriented programming (OOP) using UML (Unified Modeling Language). The information system development method uses the waterfall method. The development of the system uses the Codeigniter 4 Framework. In the case of automatic Whatsapp sending to student guardians, Node.JS is used as the Whatsapp API Gateway. Development of a school financial management information system with notifications using the Whatsapp API (application programming interface) that has been made for use by the school and is working as planned with the suitability of the effectiveness and efficiency of completing work by 100% and ease of operation by 96%.